2018
DOI: 10.3390/v10090459
|View full text |Cite
|
Sign up to set email alerts
|

Two Crinivirus-Conserved Small Proteins, P5 and P9, Are Indispensable for Efficient Lettuce infectious yellows virus Infectivity in Plants

Abstract: Genomic analysis of Lettuce infectious yellows virus (LIYV) has revealed two short open reading frames (ORFs) on LIYV RNA2, that are predicted to encode a 5-kDa (P5) and a 9-kDa (P9) protein. The P5 ORF is part of the conserved quintuple gene block in the family Closteroviridae, while P9 orthologs are found in all Criniviruses. In this study, the expression of LIYV P5 and P9 proteins was confirmed; P5 is further characterized as an endoplasmic reticulum (ER)-localized integral transmembrane protein and P9 is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…While the function of the small protein encoded by this extra ORF remains unknown, it has been shown that p9 of lettuce infectious yellows virus (LIYV) self-interacts [16], which is characteristic of RNA silencing suppressors (RSS) encoded by different viruses [17][18][19]. In line with this, it has been reported that p9 is required for establishing efficient infection and pathogenicity [20]. However, function of p9 and analogous proteins in criniviruses as RSS needs to be experimentally demonstrated.…”
Section: The Family Closteroviridae: a Brief Overviewmentioning
confidence: 99%
“…While the function of the small protein encoded by this extra ORF remains unknown, it has been shown that p9 of lettuce infectious yellows virus (LIYV) self-interacts [16], which is characteristic of RNA silencing suppressors (RSS) encoded by different viruses [17][18][19]. In line with this, it has been reported that p9 is required for establishing efficient infection and pathogenicity [20]. However, function of p9 and analogous proteins in criniviruses as RSS needs to be experimentally demonstrated.…”
Section: The Family Closteroviridae: a Brief Overviewmentioning
confidence: 99%
“…1A). In addition to PBNSPaV, other members of the family Closteroviridae also encode small molecular weight proteins (P3.5, P6, and P8) [13][14][15][16][17]. However, these proteins are different from the P6 protein in this study in coding position and homology with P6 in this study.…”
Section: Discussionmentioning
confidence: 79%
“…Contrast to PBNSPaV-P6, the subcellular localization of other small proteins encoded by viruses in the family Closteroviridae might be different. For example, the P6 protein encoded by Cucurbit Chlorotic Yellows Virus (CCYV) distributes in the cytoplasm and nucleus [13], and P5 protein encoded by lettuce infectious yellows virus (LIYV) is an endoplasmic reticulum (ER) localized integral membrane protein capable of inducing ER stress [17].…”
Section: Discussionmentioning
confidence: 99%
“…A non-virion protein, P26, which is encoded by lettuce infectious yellows crinivirus, is PD-localized and essential for viral systemic infection [13]. Small proteins P5 and P9, which are encoded by LIYV RNA2, are indispensable for efficient viral infectivity in plants [14]. Movement proteins differ among cloteroviruses; therefore, the objective of this study was to determine whether the CCYV protein P4.9 is a movement protein.…”
Section: Main Textmentioning
confidence: 99%
“…Different plant viruses use different host cell transport machinery to move from one cell to another through the PD [1721]. A previous study of LIYV P5 and P9 showed that neither protein was essential for viral infection, but that knocking out either protein led to debilitated LIYV infection [14], suggesting that these two proteins may participate in viral movement. Similarly, the P6 protein of closteroviruses BYV and CTV has been found to be involved in viral movement [1012].…”
Section: Main Textmentioning
confidence: 99%